Reduction of Lignin from Coffee Husk using Organosolve Method - Luluk Edahwati; Dyah Suci Perwitasari; Dyah Siswanti (Eksergi)
Coffeehas a significant role for the plantation sector in Indonesia. During processing of coffee, the husk is alse gonerated. Coffeefruit husk waste is usally used as an animal feed ingredient or as organic fertilizer. Coffee shell husk contains lignin and cellulose in 8.67% at 41.26%, respectively.This cellulose is rather high, that could be potential for bioethanol production. However the quality of bioethanol will increase if the lignin content in coffee leather eliminated or reduced. Organosolve method is one of the lignin separation process using organic chemicals that are environmentally friendly eg ethanol and methanol. In this lignin removal process variable is run 2 hours of cooking time, the concentration of ethanol (v / v) 10%, 20%, 30%, 40%, and 50%, while the addition of citric acid 1:12, 1:16 and 1: 18. The best result of the removal of lignin from cocoahusk occurred in 40%(v/v)ethanol  with the addition of citric acid and 1:16 for 2 hours cooking time obtained lignin content (in deposition) of 0.31% and 6.14 % lignin in the filtrate.